Natural History and Evolution of Anti-Interferon-γ Autoantibody-Associated Immunodeficiency Syndrome in Thailand and the United States - Hong, Gloria H (Clin Infect Dis, 2020)
BACKGROUND: The natural history of anti-interferon-γ (IFN-γ) autoantibody-associated immunodeficiency syndrome is not well understood. METHODS: Data of 74 patients with anti-IFN-γ autoantibodies at Srinagarind Hospital, Thailand, were collected annually (median follow-up duration, 7.5 years). Annual data for 19 patients and initial data for 4 patients with anti-IFN-γ autoantibodies at the US National Institutes of Health were collected (median follow-up duration, 4.5 years). Anti-IFN-γ autoantibody levels were measured in plasma samples. RESULTS: Ninety-one percent of US patients were of Southeast Asian descent; there was a stronger female predominance (91%) in US than Thai (64%) patients. Mycobacterium abscessus (34%) and Mycobacterium avium complex (83%) were the most common nontuberculous mycobacteria in Thailand and the United States, respectively. Skin infections were more common in Thailand (P = .001), whereas bone (P < .0001), lung (P = .002), and central nervous system (P = .03) infections were more common in the United States. Twenty-four percent of Thai patients died, most from infections. None of the 19 US patients with follow-up data died. Anti-IFN-γ autoantibody levels decreased over time in Thailand (P < .001) and the United States (P = .017), with either cyclophosphamide (P = .01) or rituximab therapy (P = .001). CONCLUSIONS: Patients with anti-IFN-γ autoantibodies in Thailand and the United States had distinct demographic and clinical features. While titers generally decreased with time, anti-IFN-γ autoantibody disease had a chronic clinical course with persistent infections and death. Close long-term surveillance for new infections is recommended.